METHOD OF CONTROL OF RATING OF COMPONENTS OF THE TRANSFORM BASED ON STRUCTURAL SATURATION OF FRAGMENTS OF AERIAL PHOTOGRAPHS - Баранник, Володимир Вікторович; Підлісний, Сергій Анатолійович; Стасев, Сергій Юрійович (Science-based technologies, 2016)
The existing methods of application of a video information resource in the state departmental establishments are considered. It is indicated the necessary of reduction of time expenditure by delivery of picture data and maintenance of compliance of restored fragments to the initial aerial photograph. Characteristics of a matrix of rating of components transforms are justified. The quantitative indices of characteristics for image sections with different structural complexity are described. The necessary for control of normalization taking into account structural complexity of aerial photographs is reasoned. The method of the adaptive normalization of components of a segment of the image with class definition of structural complexity is shown. The order of coefficients of rating for image segments with an average level of saturation is defined.